1988
DOI: 10.1002/eji.1830180608
|View full text |Cite
|
Sign up to set email alerts
|

The progression of the inflammation in established collagen‐induced arthritis can be altered by treatments with immunological or pharmacological agents which inhibit T cell activities

Abstract: Alterations in the progression of the inflammatory disease in mice with established collagen-induced arthritis (CIA) by in vivo treatments with either anti-T cell antibodies or an immunosuppressive drug, whose main targets of action are T cells, were studied. It was demonstrated that the in vivo administration of either monoclonal anti-L3T4, anti-Ly-2 or the combination of anti-L3T4 and anti-Ly-2 failed to modify the inflammatory disease after the arthritis had been initiated. Nevertheless, the progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…Van den Broek et al [28] reported a decrease in paw swelling when administering W3/25 to rats with established streptococcal cell wall-induced arthritis. In contrast, anti-CD4 MoAbs were unable to ameliorate established CIA in mice [15][16][17] or in rats [29].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Van den Broek et al [28] reported a decrease in paw swelling when administering W3/25 to rats with established streptococcal cell wall-induced arthritis. In contrast, anti-CD4 MoAbs were unable to ameliorate established CIA in mice [15][16][17] or in rats [29].…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, the disappearance of CD8 lymphocytes did not influence the chronic inflammatory response. Antibodies against CD8 molecule are also ineffective in the prevention of rat AA [31] and mouse CIA [16]. CD8 cells do not seem therefore to regulate the inflammatory response, either in the initiation or in the perpetuation of an arthritic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting results, implicating an active role of T cells in established CIA, have been proposed by Horn et a1 (12), who demonstrated that combined treatment with anti-CD4 MAb and anti-Thy-1 MAb, begun after the establishment of arthritis, prevented further advancement of the disease. In addition, Seki et a1 (3) suggested that both anti-CII antibody and cellular immunity are required for the development and perpetuation of CIA.…”
mentioning
confidence: 80%
“…The resistant Buffalo strain is reported to have a significantly lower CD4/CD8 ratio in blood, spleen and lymph node compared with the susceptible Holtzman strain, and selective depletion of CD8 + cells (with low dose cyclophosphamide) in Buffalo rats induces AA, suggesting an anti-inflammatory role for CD8 + cells in this strain [35]. In collagen-induced arthritis, although CD8 + cells are found to accumulate in rat synovial sections, anti-CD8 therapy has no effect on established arthritis in mice [36,37] but reduces the severity of arthritis in castrated female rats, suggesting a proinflammatory role in this instance [38].…”
Section: Anti-cd8 and Hgcl 2 -Induced Arthritismentioning
confidence: 99%